Bilateral internal thoracic artery grafting: propensity analysis of the left internal thoracic artery versus the right internal thoracic artery as a bypass graft to the left anterior descending artery. (22nd October 2019) - Ogawa, Shinji; Tsunekawa, Tomohiro; Hosoba, Soh; Goto, Yoshihiro; Kato, Takayoshi; Kitamura, Hideki; Tomita, Shinji; Okawa, Yasuhide
Abstract: : OBJECTIVES: To compare different configurations of the bilateral internal thoracic arteries for the left coronary system and examine early and late outcomes, including mid-term graft patency. METHODS: We reviewed 877 patients who underwent primary isolated coronary artery bypass grafting using in situ bilateral internal thoracic arteries [ in situ right internal thoracic artery (RITA)-to-left anterior descending artery (LAD) grafting, n = 683; in situ left internal thoracic artery (LITA)-to-LAD grafting, n = 194]. We compared mid-term patency between the grafts. Propensity score matching was performed to investigate early and long-term outcomes. RESULTS: The 2-year patency rate for RITA-to-LAD and LITA-to-LAD grafts were similar. Multivariate analysis revealed that RITA-to-non-LAD anastomosis ( P = 0.029), postoperative length of stay ( P = 0.003) and chronic obstructive pulmonary disease ( P = 0.005) were associated with graft failure. After statistical adjustment, 176 propensity-matched pairs were available for comparison. RITA-to-LAD grafting enabled a more distal anastomosis. Kaplan–Meier analysis revealed that the incidences of death, repeat revascularization and myocardial infarction were significantly higher in the LITA-to-LAD group among both the unmatched and matched samples ( P = 0.045 and 0.029, respectively). CONCLUSIONS: The mid-term patency and outcomes of RITA-to-LAD grafting are good and reduces future cardiac event, in contrast to LITA-to-LAD grafting.